Coalitions for Children: A Comparative Analysis of Child Protection Policies in Indonesia and the United States - Haniyah Shofiyatul Aini; Antun Mardyanta; Bintoro Wardiyanto (University of Merdeka Malang, 2026)
This study compares the role of advocacy coalitions in forming child protection policies in the United States and Indonesia, looking at the problems that arise from their different political and governance systems. The Family First Prevention Services Act (FFPSA) in the United States aims to reduce the number of children in foster care by encouraging family-centred interventions. However, its implementation has been uneven across states due to political opposition, a lack of resources, and the fact that the federal system is not highly centralized. Consequently, marginalized communities, especially in rural regions, encounter limited access to child protection services. In Indonesia, Child Protection Law No. 35 of 2014 faces analogous challenges in rural areas, where local governments lack the necessary resources, political commitment, and coordination with national entities to effectively implement child protection legislation. This study suggests that policies work better in cities than in rural areas. For example, Jakarta benefits from better policy implementation and resource allocation. The findings show how important it is to improve inter-agency collaboration, strengthen local governance, and get more political support to fix the problems with child protection services. To make sure that all children are equally protected, both countries need to focus on implementing policies at the local level, especially for vulnerable children in areas that don't get enough services.